Analysis of the Online Learning Process for Early Childhood Education Students, Faculty of Education, Universitas Negeri Medan during the Covid-19 Pandemic - Suri Handayani Damanik; Isa Hidayati; May Sari Lubis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study is to describe the online learning process for early childhood education students, faculty of education, Universitas Negeri Medan and Learning Plans as the product development. This research is a quantitative descriptive using survey method which is collected online. The research variable studied was the online learning process of students. The measuring aspects studied in this study include aspects of learning planning, learning activities, learning strategies, learning media and technology, learning assistance services. The data collection method used purposive sampling technique. The instrument used is in the form of a questionnaire using the scale method. Based on the results of data analysis, it was concluded that more than 50% of the students gave very good assessments of the 5 aspects assessed.